Role Of Parents In The Success Of Children Autism - Merri Sri Hartati (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This study aimed to explain the role of parents in accompanied autism children. Research conducted in this study was qualitative with the type of case study. The selection of subjects was based on consideration of being a child with the category of autism, graduated from an inclusive school, and being accepted as a student through a regular test track. The methods used in the study were interviews, observation, and documentation. The results showed that children have a decisive role towards successful children, and helped in supported children, tried as much as possible with therapy, analyzed, and encouraged the talents and interested of children. A suggestion from the findings of this study is that there is a need for individual classes for parents about parenting education for autism children so that parents can help autism children find their talents